Characterisation of a monoclonal antibody recognising the CD3 epsilon chain of the bovine T cell receptor complex - MacHugh, Niall D.; Mburu, J.K.; Hamilton, M.J.; Davis, W.C. (Elsevier, 1998)
The characterisation of a monoclonal antibody (mAb), designated MM1A, which reacts with an antigen molecule on the surface of bovine alfa beta and gama delta TcR+ T cells is described. The mAb immunoprecipitated a series of polypeptides of 21 kDa, 22 kDa, 36 kDa and 44 kDa which is consistent with it recognising the TcR/CD3 complex. COS cells, transfected with a cDNA encoding the bovine CD3e chain, reacted with mAb MM1A indicating that the epitope recognised is on the chain of the complex and confirming the mAb recognised bovine CD3.